BENTUK TARI ZAHIFA PADA UPACARA PERKAWINAN MASYARAKAT ARAB DI KOTA MEDAN - Sinta Wijayanti (Gesture: Jurnal Seni Tari, 2017)
This study aimed to describe Zahifa Dance Forms In Marriage Ceremony Arab Society in Medan include: (1) the function of dance, (2) form Dance Zahifa In Marriage Ceremony Arabs in the city of Medan.  The theoretical foundation of this research is grounded in the theory of functions and the theory that examines forms Zahifa dance based on dance, Typewriter and accompaniment, makeup and clothing, as well as the venue floor pattern. This study used a qualitative descriptive approach. This research data is, functions and forms of dance Zahifa In Marriage Ceremony Arabs in the city of Medan. The data used is Zahifa dance at Al Fairouz community in Medan. Data were collected with a population of 11 people comprising 1 figure and 10 dancers dance Zahifa, observation, interview, and literature study. Data were analyzed using descriptive techniques. The results of this study as follows. 1) the existence of the Arab city of Medan, where the Arab community in the city of Medan is still very rare, the Arab community in the city of Medan strengthening of family by setting up a container such as community organizations. 2) The wedding ceremony Arab community in the city of Medan. 3) Function Zahifa dance on Arab communities in the city of Medan, namely as a means of ceremonies, performances and entertainment facilities. 4) The form of presentation of dance Zahifa the Arab community in the city of Medan, namely (a) motion, (b) the music or accompaniment, (c) cosmetology, (d) the pattern of the floor, (e) the venue.